Modelling of multimode selenide-chalcogenide glass fibre based MIR spontaneous emission sources - Sujecki, S.; Sójka, L.; Bereś-Pawlik, E.; Piramidowicz, R.; Sakr, H.; Tang, Zhuoqi; Barney, Emma R.; Furniss, David; Benson, Trevor M.; Seddon, Angela B. (IEEE, 2017)
Chalcogenide glass fibres have been demonstrated as a suitable medium for the realisation of spontaneous emission sources for mid-infrared photonics applications with a particular emphasis on sensor technology. Such sources give a viable alternative to other solutions due to their potentially low cost, high reliability and robustness when pumped using commercially available semiconductor lasers. We present a comprehensive analysis of the properties of selenide-chalcogenide glass fibres applied as spontaneous emission sources. We extract the modelling parameters from measurements using in house fabricated bulk glass and fibre samples. We apply the well-established rate equations approach to determine the level populations, the distribution of the photon intensity within the fibre and the output power levels. We compare the modelling results with experiment.